Responding to the Global Issues of Digitally Differentiated Arabic Learning for Students with Special Needs in Integrated Islamic Elementary Schools - Suyudi, Muhamad; Putra, Wahyu Hanafi; Witasari, Rinesti (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This study aims to describe the application of digitally differentiated Arabic language learning for students with special needs in the Integrated Islamic Elementary School at SDIT Darul Falah Sukoreo Ponorogo. It is case study research involving seven students with special needs at SDIT Darul Falah. The data collection technique uses observation, in-depth interviews, and documentation. Meanwhile, data analysis is carried out by data reduction, data presentation, and conclusions drawn. The study results showed that Arabic at SDIT Darul Falah Sukorejo Ponorogo is a lesson within the framework of an informal curriculum that must be taught to regular students and students with special needs. Second, the Arabic learning methodology for students with special needs focuses on the self-esteem approach, which aims to increase student confidence, which can affect Arabic's motivation and learning outcomes. Third, Digital Differentiated Arabic Language Learning for students with special needs uses more digital media such as audio-visual media, animated graphics, and educational and social media; this effort is carried out on the principle of second language learning (B2), which must involve the needs of students, especially students with special needs. Digitally differentiated Arabic learning has shown its effectiveness in improving the quality of learning. This digital media can help students with special needs to understand and interact with Arabic more easily. Teachers at SDIT must be trained to use the self-esteem approach and digital technology to learn Arabic. This is so teachers can effectively teach students with special needs.